An Analysis of the Claims and Compensation Available to Victims as a Result of Damage in Outer Space - Olatinwo, Khafayat (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2024)
The legal maxim ‘Ubi Jus IbiRemedium’ is to the extent that it is expected that injured party gets remedy for the injury suffered. Unlike individuals cum domestic activities/legal system, to determine who is/are wrong in outer space activity, the result of damage, is quite dicey. Firstly, states are of course parties to space regimes as such expected to be actors in space activities to which one or many states jointly with international intergovernmental organisations can be the one conducting the activities (launching state) that led to the damage or even the injured party.Secondly, outer space with its activities is an international subject regulated majorly by international law, so that questions involving what amounts to damage, who can present a claim, the quantum of damages, determination of adequate compensation, parties to a claim amongst others are the subject of analysis in this article. To answer these questions,this article intends to examine the relevant international law i.e. International Space Law and Customary International Law, on the claims and compensation available to victims of damage in the course of outer space activities, assess the adequacies of the claims and compensation and proffer recommendations where necessary.